2021
DOI: 10.1093/ije/dyab002
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity rebound and cardiometabolic health in childhood: results from the Generation XXI birth cohort

Abstract: Background We aimed to evaluate the association of adiposity rebound (AR) timing on cardiometabolic health in childhood. Methods Participants were part of the Generation XXI birth cohort, enrolled in 2005/2006 in Porto. All measurements of the child’s weight and height performed by health professionals as part of routine healthcare were collected. Individual body mass index (BMI) curves were fitted for 3372 children, using mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…We excluded 8,512 records that met one of the following exclusion criteria: null value for all the measures ( n = 6,845), duplicate records ( n = 982), and records with fewer than three measurement times ( n = 685). We selected only children who had at least three measurement times (weight and length/height at the same measurement, and only one measurement per month) during their 1st and 80th months of age for growth trajectory modeling ( 24 ). To avoid influential points, high leverage points, and outliers, we also removed records of children with abnormal growth patterns ( n = 153).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We excluded 8,512 records that met one of the following exclusion criteria: null value for all the measures ( n = 6,845), duplicate records ( n = 982), and records with fewer than three measurement times ( n = 685). We selected only children who had at least three measurement times (weight and length/height at the same measurement, and only one measurement per month) during their 1st and 80th months of age for growth trajectory modeling ( 24 ). To avoid influential points, high leverage points, and outliers, we also removed records of children with abnormal growth patterns ( n = 153).…”
Section: Methodsmentioning
confidence: 99%
“…All data of multiple observations obtained in early life regarding children's age, weight, and length/height were used to estimate BMI and its trajectories. To guarantee the quality of BMI trajectory fitting, children with no measurement between the 1st and 12th months of age were excluded for AP estimation ( n = 3,711), and children with no measurement after 18 months of age or between 42 and 84 months of age were excluded for AR estimation ( n = 457) ( Figure 1 ) ( 24 ). The individual-specific BMI trajectory from the 1st to 80th months of age was fitted using non-linear mixed-effect models with natural cubic spline functions for age to capture the non-linear trend ( 14 , 24 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Every anthropometric measurement taken for the children was recorded by the health care professionals. We only selected children who had at least three anthropometric measurements (weight and length/height at the same assessment and only one measurement per month) during their 1st and 80th months of age for growth trajectory fitting to identify their AP and AR timing [ 62 ]. Additionally, information concerning the parental ages at delivery, parental education levels, gestational weeks, delivery modes, birth weight and birth length was retrieved from their birth records.…”
Section: Methodsmentioning
confidence: 99%
“…The growth data were available in 13 612 children who had at least three anthropometric measurements during their first and 80th months of age. Their growth trajectories were fitted [ 62 ], and the AP and AR could not be estimated for 3708 and 2343 children, respectively. In our study, 9904 children with estimable AP and 11 269 children with estimable AR were found.…”
Section: Methodsmentioning
confidence: 99%